Stable and radiogenic isotope studies of tourmaline: an overview - Jiang,S.Y. (Journal of the Czech Geological Society, 1998)
This paper presents an overview on stable isotope studies of O, H, B and Si, and radiogenic isotope studies of Rb-Sr, Sm-Nd, Pb, and K-Ar in tourmaline from various geological settings. Tourmaline O-H isotopic compositions are good indicators of the sources of hydrothermal fluids and origin of the rocks and ore deposits, and can provide information regarding temperatures of tourmaline formation. Based on δ18O and δD values of tourmaline, modified seawater has been distinguished from several massive sulfide deposits, and metamorphic fluids were responsible for the formation of many hydrothermal gold deposits. There are some problems in the previously published, empirical calibrated oxygen and hydrogen isotope fractionation equations of quartz-tourmaline and tourmaline-water. Hence, new empirically calibrated O-H isotope fractionation equations with high correlation coefficients are presented in this paper. In addition, an experimentally determined hydrogen isotope fractionation factor between tourmaline and water at temperatures > 350 °C has recently been published (Geo-Qian 1997). Wide variations in δ11B values of tourmaline exist from various environments. Controls over the boron isotopic compositions of tourmaline are principally compositions of the source rocks, water/rock ratios, seawater entrainment, formational temperatures, and regional metamorphism. Tourmaline δ11B values are useful for distinguishing between marine and non-marine evaporitic boron sources. Using δ30Si values, it is possible to distinguish between detrital and hydrothermal sources for Si in tourmalinite, silicon isotopes could be used as effective paleo-environmental indicators. The Sr-Nd isotopic compositions of tourmaline have major implications for source reservoirs and the nature of hydrothermal fluids, and can yield tourmaline formation ages in some cases. Pb isotope studies of tourmaline obtained by stepwise Pb leaching techniques have been proven to be a good geochronometer. Tourmaline K-Ar ages may represent cooling ages with very high closure temperatures. However, only the 40Ar/39Ar dating of tourmaline provides unambiguous ages for tourmaline with a complex metamorphic history. Overall, results show that isotopic studies of tourmaline are powerful geochemical tools for tracing the source of hydrothermal fluids and their solutes, for constraining the origin of tourmaline-bearing rocks and ore deposits, and for dating tourmalinisation and associated hydrothermal alteration, mineralisation, or metamorphism.
Keywords: tourmaline; isotopes; hydrogen; oxygen; boron; silicon; strontium; neodymium; lead; argon